Respuesta :

Answer:

3x + 2 = 59

3x = 59 - 2

3x = 57

x = 19

2x + 12 = 4x

2x - 4x = -12

-2 x = -12

x = -12/ -2

x = 6

[tex]answers \\ 1. \: \: 15 \\ 2. \: \: 9 \\ 3. \: 19 \\ 4. \: \: 6 \\ solution \: \\1. \: \: x = 6 \\ y = 3 \\ x(x - y) - y \\ = 6(6 - 3) - 3 \\ = 6 \times 3 - 3 \\ = 18 - 3 \\ = 15 \\ 2. \: \frac{x {y}^{2} }{x} \\ = \frac{6 \times {3}^{2} }{6} \\ = \frac{6 \times 9}{6 } \\ = \frac{54}{6} \\ = 9 \\ 3. \: \: 3x + 2 = 59 \\ or \: 3x = 59 - 2 \\ or \: 3x = 57 \\ or \: x = \frac{57}{3} \\ x = 19 \\ 4. \: \: \: \: 2x + 12 = 4x \\ \: \: \: or \: 2x - 4x = - 12 \\ or \: - 2x = - 12 \\ or \: x = \frac{12}{2} \\ x = 6 \\ hope \: it \: helps \\ good \: luck \: on \: your \: assignment[/tex]

ACCESS MORE